Analisis Strategi Pemasaran Dalam Meningkatkan Produk Pada PT Jaminan Pembiayaan Askrindo Syariah KC Medan - Etikarahmi Siregar; Atika (CV. Ulil Albab Corp, 2022)
PT Askrindo Financing Guarantee is a financing guarantee company and one of the State-Owned Enterprises (BUMN) engaged in Insurance or Sharia Guarantee with the aim of developing the National Economy and playing an active role in the global market, the company is present as a pioneer. This study aims to analyze the marketing strategy undertaken by PT Guarantee Financing Askrindo Syariah KC Medan in improving a product marketing to Islamic Banks (Makful Lahu). The method used is descriptive qualitative method. With the analysis method with interview factors and previous data. This research was conducted so that the company PT Guarantee Financing Askrindo Syariah continues to be more and more consistent as a financing guarantee institution in the marketing strategy of a product. Meanwhile, the problem is at PT Askrindo Syariah Financing Guarantee KC Medan Product marketing such as promotion to Islamic banks (Makful Lahu). This problem is due to the lack of knowledge of Islamic banks regarding the existence of a financing guarantee. Keywords: strategy, marketing, product